Retrieval of Dust Properties From Spectral Snow Reflectance Measurements - Kokhanovsky, Alexander; Di Mauro, Biagio; Garzonio, Roberto; Colombo, Roberto (Frontiers in Environmental Science, 2021)
In this paper, we present a simplified algorithm to retrieve snow grain size, dust mass absorption coefficient and dust mass concentration from spectral diffuse reflectance measurements at three wavelengths located in the visible and near infrared. The theoretical model is then compared with field spectroscopy data collected in different days from an automated spectrometer in the Alps.